Perilaku Caring Perawat dalam Memberikan Asuhan Keperawatan di Salah Satu RS di Kabupaten Indramayu - Aeni, Wiwin Nur; Winani, Winani; Sutioso, Hendri (Jurnal Keperawatan Profesional, 2019)
Nurses are required to have sensitivity and ability to support patients' trust and welfare through caring behavior. Nurse caring behavior will have a significant influence on the patient's care process in the hospital. The aim of study was to determine the description of nurse’s caring behavior in nursing services in one hospital in Indramayu Regency 2017. The study used descriptive methode. Population was patients in the Inpatient Room of one hospital in Indramayu Regency. Samples were 96 respondents which selected by accidental sampling technique. Humanistic and Altruistic caring behaviors of nurses were 91.7%, provide trust were 82.3%, foster sensitivity to themselves and others were 69.8%,  develop a relationship between mutual trust in patients were 77.1%, increase and receive expressions of positive and negative feelings towards patients were 77.1%, solving problems for decision making were 65.6%, increased learning and interpersonal teaching were 71.9%, creating supportive physical, mental, sociocultural, and spiritual environments were 81.3%, provide guidance in satisfying needs were 69.8%, and allowing for phenomenological stress to patient mental-growth and maturity pressure were 52.1%. Nursing caring behavior in the Inpatient Room of one hospital in Indramayu Regency were 53.1%.  Keywords: Caring Behavior, Nurses, Service